The Knowledge Building of Construction Process of Bali Arya’s Architecture: Interpretation of the Manuscript Asta Kosala Kosali - Arthana, I Nyoman Nuri (Journal of Architectural Research and Education, 2019)
Bali has written rules about building procedures which are traditionally are still used today. The rules are written in an ancient manuscript in the form of a palm leaf known as Asta Kosala Kosali (AKK). The AKK manuscript has been around since the arrival of the Aryans from the Majapahit kingdom to Bali, therefore the architectural products produced in this period are called Bali Arya’s architecture. Based on the contents of the AKK script, the disclosure of architectural knowledge is carried out using an architectural perspective in the context of construction. This perspective and context used show that this research is different from previous studies of the AKK manuscripts that use cultural, anthropological, and historical perspectives. This study places the AKK script as the main object of research, therefore the method used is to apply hermenetic operations or called interpretations. Through this research architectural knowledge can be formulated in the context of construction, namely; 1) the basic foundation of the construction process that is carried out is truth in the process, obedience to the principles of building and the achievement of pleasure in each stage and its results. 2) The principles applied in the construction process, technically is the assembly of construction components starting from the building body, applying the principle of strong columns -weak beams, prioritizing the sustainability of materials, construction and building, and using rational composition of regular geometric shapes to achieve beauty . 3) The basic concept as the ultimate goal of the construction process is the balance and harmony of the relationship between humans, nature and God. These three formulations are components of the building of Bali Arya’s architectural knowledge in the context of the construction process. Keywords: knowledge; construction process; Bali Arya’s architecture; interpretation